The greatest sentence ever written - Isaacson, Walter (Simon & Schuster, 2025)
"To celebrate America's 250th anniversary, Walter Isaacson takes readers on a ... deep dive into the creation of one of history's most powerful sentences: 'We hold these truths to be self-evident, thatall men are created equal, that they are endowed by their Creator with certain unalienable Rights, that among these are Life, Liberty, and the pursuit of Happiness.' Drafted by Thomas Jefferson and edited by Benjamin Franklin and John Adams, this line lays the foundationfor the American Dream and defines the common ground we share as a nation. Isaacson unpacks its genius, word by word, illuminating thethen-radical concepts behind it"--